Interactive Al-Quran Learning Media in Raising Elementary School Students' Learning Motivation - R Nurhayati; Suwito, Agus; Syamsir; Ningsih, Diarti Andra; Qisthy, Nurul; Damayanti, Riska; Ramadhani, Fakhri (Universitas Islam Ahmad dahlan, 2025)
This article discusses the development of interactive Qur'anic learning media aimed at enhancing student motivation in elementary schools. Through the library research method, this study analyzes various relevant sources regarding the use of interactive media in education, particularly in the context of Qur'anic learning. Interactive media is an innovation in how we engage with information and content in the digital era. For instance, mobile applications and digital platforms have proven effective in capturing students' interest and increasing their engagement in the learning process. Furthermore, research shows that integrating Qur'anic values into learning media not only enhances students' religious understanding but also contributes to their character development and learning motivation. The results of this study are expected to provide valuable insights for educators and media developers in creating effective and engaging learning tools, as well as fostering technology-based learning innovations, particularly for Qur'anic education.